PREDATION OF COTTON LEAFWORM 1ST INSTAR LARVAE, ALABAMA-ARGILLACEA [LEP, NOCTUIDAE] - Gravena, S.; Dacunha, H. F. (Lavoisier Abonnements, 1991)
Natural predation first instar larvae of the cotton leafworm (CLW) A. argillacea was studied in cotton fields in Jaboticabal, São Paulo State, Brazil, during 1986. The presence of naturally occurring arthropod predators showed a first instar larvae predation rate of 78.6 and 88.9% after 24 h and 48 h of exposure, respectively. A predator prey ratio of 1 : 1 (1 CLW key predator per 1 prey/plant) maintained a level of no more than 1 CLW small larvae per plant. The most evident arthropod predators in the studied fields were: beetles (Coleoptera: Coccinellidae), ants Pheidole sp. and Conomyrma sp.; Dermaptera Doru lineare (Eschs); Hemiptera Geocoris sp., and Orius insidiosus Say; and the spiders Theridion volubile, Chrysso pulcherrima, Misumenops sp., Chiracanthium sp., and Oxyopes salticus Hentz.
Keywords: COTTON LEAFWORM; ALABAMA-ARGILLACEA; Biological control; PREDATION